PERAN PARTAI POLITIK DI DALAM PELAKSANAAN PENDIDIKAN POLITIK DALAM RANGKA UNTUK MENINGKATKAN PARTISIPASI DAN INISIATIF MASYARAKAT DALAM PROSES PEMILU DI KOTA SEMARANG - Lutter Ariestino; Sri Kusriyah (Jurnal Hukum Khaira Ummah, 2018)
The role of Political Parties in the provision of political education to the public is a duty that must be implemented to realize the ideals of this nation's democracy, with the great participation of the community in voting in the general election, especially the people in Semarang City. The high number of votes given by the people in the general election indicates the role of political parties in providing political education materials.Political education given to the community implemented by political parties in the city of Semarang include: Gerindra Party, Golkar, and Democrats do not run as expected, therefore the author makes this thesis with the formulation of the problem: 1. The role of political parties in providing political education to community of Semarang City. 2. Does the political education undertaken provide an innovative impact and the active role of the community in following the elections. 3. Constraints and solutions of political education from political parties in Semarang City.Writing this thesis aims to determine the implementation of political education conducted political parties in the city of Semarang whether it is in accordance with the ideals of democracy as stipulated in Law No. 2 of 2011 on Political Parties.The results of this study indicate that political education conducted by political parties in Semarang City has been successful with marked improvement of public vote and general election. Keywords: Role, Political Education, Political Party